Manufacturing and Characterization of III-V on Silicon Multijunction Solar Cells. (August 2016) - Veinberg-Vidal, Elias; Dupré, Cécilia; Garcia-Linares, Pablo; Jany, Christophe; Thibon, Romain; Card, Tiphaine; Salvetat, Thierry; Scheiblin, Pascal; Brughera, Céline; Fournel, Frank; Desieres, Yohan; Veschetti, Yannick; et al.
Abstract: Tandem GaInP/GaAs//Si(inactive) solar cells were manufactured by direct wafer bonding under vacuum. At this early stage, an inactive silicon substrate was used (i.e. n+ Si substrate instead of an active n-p Si junction). Bonded devices presented an S-shaped J-V curve with a kink close to V oc caused by a built-in potential barrier at the III-V//Si interface that reduces the fill factor and therefore the efficiency of the device by 7% compared to the stand-alone GaInP/GaAs tandem cells. Nevertheless, losses in J sc and V oc caused by the bonding process, account for less than 10%. AlGaAs single junction cells, designed to be bonded on a silicon cell for low concentrator photovoltaics (LCPV), were also manufactured reaching an efficiency of 15.9% under one sun AM1.5G spectrum for a 2cm 2 cell.